ANALYSIS OF INFLAMMATORY DISEASES OF THE THROAT AND THE ANTIBIOTICS USED IN THEM - Yodgorova N.T., Mamanov J.B., Makhsudkhojayeva Kh.M., (Central Asian Journal of Medicine, 2025)
Research objective: To determine the etiology of throat diseases in the population of the Republic of Uzbekistan in 2023-2024 and to describe their antibiotic resistance status. Materials and methods: The infections detected in patients with throat infections from the second half of 2023 to the beginning of 2024 at the Bacteriological Laboratory of the Tashkent Medical Academy of the Republic of Uzbekistan, as well as the microorganisms identified in them and their antibiotic sensitivity were analyzed. Bacteriological and statistical methods were used. Analysis and discussion of results: During this 6-month period, 200 patients (25 men, 175 women) complained of inflammatory diseases in the throat. When samples taken from them were laboratory diagnosed, more than 400 different bacteria were detected in all patients (Streptococcus ssp.-60%, Candida ssp.-30%, Staphylococcus aureus-10%). Conclusion: As a result of the analysis, we can see that women are more likely to get sore throats (88%) (average age was 27). The most common cause of inflammation is Streptococcus ssp (60%), and the most effective antibiotics for the bacteria: Sulfamethoxazole, Levofloxacin, Amoxicillin and Ampicillin gave good results.